DENTAL CARIES PREVENTION THROUGH EDUCATION AND GIVING FLUORIDE FOR ELEMENTARY SCHOOL STUDENTS: PENCEGAHAN KARIES GIGI BERBASIS EDUKASI DAN PEMBERIAN FLUOR PADA SISWA SEKOLAH DASAR - Jumriani; Liasari, Ira; Thioritz, Ernie; Septa, Badai; Asriawal; Priyambodo, R. Ardian (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Dental caries among elementary school students remain high to this day. The occurrence of dental caries is often linked to poor oral hygiene, leading to damage in the tooth's hard tissues. A promotive and preventive approach is necessary, especially for elementary school students during the critical period of transitioning from primary to permanent dentition. Objective: This community engagement program aimed to improve dental hygiene and oral health among elementary school students through education, mass toothbrushing activities, and giving topical fluoride. Method: The methodology included dental hygiene and caries examinations, followed by educational sessions, mass toothbrushing activities, and the administration of topical fluoride to protect teeth from caries attacks. The evaluation of success is determined by comparing the oral hygiene index before and after the activity. Results: The evaluation results indicate that the educational outreach and mass toothbrushing campaign have had a positive impact on improving the overall oral hygiene levels of students. The number of students classified under the "good" category has increased, while those in the "fair" and "poor" categories have shown a decrease. Conclusion: The comprehensive approach, comprising dental health education, mass toothbrushing sessions, and the administration of fluoride during this community service initiative, has proven to yield positive benefits in enhancing the oral hygiene of students.